Determination of Ultratrace Amounts of Bismuth in Water Samples by Electrothermal Atomic Absorption Spectrometry (ET-AAS) After Cloud Point Extraction - Javad Poursharifi, Mohammad; Moghimi, Ali (Asian Journal of Chemistry, 2010)
A new approach for a cloud point extraction electrothermal atomic absorption spectrometric method was used for determining bismuth. The aqueous analyte was acidified with sulfuric acid (pH 3.0-3.5). Triton X-114 was added as a surfactant and sodium diethyldithiocarbamate was used as a complexing agent. After phase separation at 50 ºC based on the cloud point separation of the mixture, the surfactantrich phasewas diluted using tetrahydrofuran. Twenty microliters of the enriched solution and 10 μL of 0.1 % (w/v) Pd(NO3)2 as chemical modifier were dispersed into the graphite tube and the analyte determined by electrothermal atomic absorption spectrometry. After optimizing extraction conditions and instrumental parameters, a preconcentration factor of 195 was obtained for a sample of only 10 mL. The detection limit was 0.04 ng mL-1 and the analytical curve was linear for the concentration range of 0.04-0.70 ng mL-1. Relative standard deviations were < 5 %. The method was successfully applied for the extraction and determination of bismuth in samples water.